A framework on eudaimonic well-being in destination competitiveness - Sarmento, E. M.; Loureiro, S.; Mendes, Z.; Monteiro, J. M.; Fernandes, S. (Tourism and Hospitality, 2025)
This research proposes a framework for Eudaimonic well-being in destination competitiveness. This framework is based on the theoretical Ritchie and Crouch’s model (1993, 2000, 2003) and the recent theoretical notion that a travel trip may influence life satisfaction through tourists’ experiences. We conducted a qualitative study based on 34 in-depth interviews with key tourism stakeholders in Cape Verde, a small island developing country (SIDS) dependent on the tourism sector. The findings contribute to identifying specific sources of positive and negative effects that may affect the tourists’ and residents’ overall sense of well-being and thus affect the overall destination competitiveness.